Aetiology of acute paediatric gastroenteritis in Bulgaria during summer months: prevalence of viral infections. Issue 3 (March 2015) - Mladenova, Zornitsa; Steyer, Andrej; Steyer, Adela Fratnik; Ganesh, Balasubramanian; Petrov, Petar; Tchervenjakova, Tanja; Iturriza-Gomara, Miren
Abstract : Paediatric acute gastroenteritis is a global public health problem. Comprehensive laboratory investigation for viral, bacterial and parasitic agents is helpful for improving management of acute gastroenteritis in health care settings and for monitoring and controlling the spread of these infections. Our study aimed to investigate the role of various pathogens in infantile diarrhoea in Bulgaria outside the classical winter epidemics of rotavirus and norovirus. Stool samples from 115 hospitalized children aged 0–3 years collected during summer months were tested for presence of 14 infectious agents – group A rotavirus, astrovirus, Giardia, Cryptosporidium and Entamoeba using ELISAs; norovirus by real-time RT-PCR; picobirnavirus and sapovirus by RT-PCR; adenovirus using PCR, and Salmonella, Shigella, Escherichia coli, Yersinia and Campylobacter using standard bacterial cultures. Infectious origin was established in a total of 92 cases and 23 samples remained negative. A single pathogen was found in 67 stools, of which rotaviruses were the most prevalent (56.7 %), followed by noroviruses (19.4 %), enteric adenoviruses (7.5 %), astroviruses (6.0 %), bacteria and parasites (4.5 % each) and sapoviruses (1.4 %). Rotavirus predominant genotypes were G4P[8] (46.3 %) and G2P[4] (21.4 %); for astroviruses, type 1a was the most common, while the GII.4/2006b variant was the most prevalent among noroviruses. Bacteria were observed in five cases, with Salmonella sp. as the most prevalent, while parasites were found in ten stool samples, with Giardia intestinalis in five cases. The results demonstrated high morbidity associated with viral infections and that rotavirus and norovirus remain the most common pathogens associated with severe gastroenteritis during summer months in Bulgaria, a country with a temperate climate, and significant molecular diversity among circulating virus strains. Abbreviations: AdV, adenovirus; AGE, acute gastroenteritis; AstV, astrovirus; NoV, norovirus; PBV, picobirnavirus; RdRp, RNA-dependent RNA polymerase; RV, rotavirus; SaV, sapovirus.